1994
DOI: 10.1007/bf00223649
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome assignment of four photosynthesis-related genes and their variability in wheat species

Abstract: Copy numbers of four photosynthesis-related genes, PhyA, Ppc, RbcS and Lhcb1 (*)1, in wheat genomes were estimated by slot-blot analysis, and these genes were assigned to the chromosome arms of common wheat by Southern hybridization of DNA from an aneuploid series of the cultivar Chinese Spring. The copy number of PhyA was estimated to be one locus per haploid genome, and this gene was assigned to chromosomes 4AL, 4BS and 4DS. The Ppc gene showed a low copy number of small multigenes, and was located on the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
0
19
0
2
Order By: Relevance
“…Total DNA was isolated from seedlings of common wheat (T. aestivum cv CS) and from nullisomic-tetrasomic as well as ditelosomic lines of CS (Sears, 1965), as described previously (Ogihara et al, 1994). By tracing the SNP sites in the contigs, primer sets were designed using Primer3 software (Rozen and Skaletsky, 2000) so as to specifically amplify each multigene (Table II).…”
Section: Construction Of Dendrogram Showing Phylogenetic Relationshipmentioning
confidence: 99%
“…Total DNA was isolated from seedlings of common wheat (T. aestivum cv CS) and from nullisomic-tetrasomic as well as ditelosomic lines of CS (Sears, 1965), as described previously (Ogihara et al, 1994). By tracing the SNP sites in the contigs, primer sets were designed using Primer3 software (Rozen and Skaletsky, 2000) so as to specifically amplify each multigene (Table II).…”
Section: Construction Of Dendrogram Showing Phylogenetic Relationshipmentioning
confidence: 99%
“…These inconsistencies found in wheat chromosomes were mainly due to the rearrangements involving chromosomes arms 4AL, 5AL, and 7BS in the polyploid wheats . The A genome of polyploid wheats was shown to be most closely related to that of T. urartu, showing differentiation from T. monococcum and T. boeoticum (Nishikawa, 1983;Dvorak et al, 1993;Takumi et al, 1993;Ogihara et al, 1994b). Actually, the hybrids between T. urartu and T. monococcum are sterile (Johnson and Dhaliwal, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the hybrids between T. urartu and T. monococcum are sterile (Johnson and Dhaliwal, 1976). On the other hand, the A genomes of T. monococcum (cultivated) and T. boeoticum (wild relative) were classified into one group due to the good crossability and chromosome pairing between the two species (Kihara et al, 1929) and their common molecular markers (Nishikawa, 1983;Dvorak et al, 1993;Takumi et al, 1993;Ogihara et al, 1994b).…”
Section: Introductionmentioning
confidence: 99%
“…Exon 1 encodes a transit peptide of 46 amino acids plus 2 amino acids of the mature protein and exon 2 encodes the major part of the mature protein which consists of 127 amino acids (Broglie et al, 1983). Galili et al (1991) estimated that there were at least 22 copies of rbcS in the hexaploid wheat genome, while Ogihara et al (1994) reported the presence of approximately 100 copies. The wheat rbcS genes were classified into four subfamilies based on differences in the Southern hybridization pattern using the 3' non-coding region as probe (Galili et al, 1992).…”
Section: Introductionmentioning
confidence: 99%